Patterns of distant metastasis in head and neck cancer at presentation: Implications for initial evaluation. (January 2019) - Liu, Jeffrey C; Bhayani, Mihir; Kuchta, Kristine; Galloway, Thomas; Fundakowski, Christopher
Highlights: Head and neck cancer patients uncommonly present with distant metastasis. The risk of distant metastasis is associated with tumor factors such as TNM stage. Patterns of distant metastasis presentation informs appropriate selection of tests for workup and evaluation. Chest CT scan may provide adequate distant metastasis evaluation in selected cases. Abstract: Importance: Evaluation of distant metastasis (DM) is part of every new cancer evaluation. Understanding DM presentation patterns may impact the imaging workup of Head and Neck Squamous Cell Carcinoma (HNSCC). Objective: Examine the frequency and location of DM at presentation in HNSCC. We hypothesize that DM are rare, and the lung is the most common site for DM. Secondary evaluation includes identifying patient and tumor factors predictive of DM, and the implications for selection of workup imaging. Design: Data from the National Cancer Data Base (NCDB) from 2010 to 2015 were analyzed. Subsites evaluated included oral cavity, oropharynx, larynx, hypopharynx, and nasopharynx. Sites of distant metastasis were evaluated in available cases and analyzed. Setting: Population based database study. Results: 151, 730 cases were available for analysis. Nasopharynx had the highest percentage of M1 disease (9.1%) followed by hypopharynx (7.3%). Excluding the nasopharynx (NP), 3.1% of cases were reported as M1. Advanced T-stage, positive N-stage, and N3 status were all predictors of M1 status on univariate and multivariate analysis for all subsites (P < 0.05). Where site of metastasis was available, most (53.1%) DM cases presented with at least lung involvement. In nasopharynx cancers, only 32.8% of DM included the lung. Conclusions and relevance: Distant metastasis in HNSCC are rare events. PET/CT offers many advantages, but for routine distant metastasis evaluation in HNSCC, CT scan of the chest may be more cost-effective.